Cardiovascular biomarkers in patients with cancer and their association with all-cause mortality. Issue 23 (28th September 2015) - Pavo, Noemi; Raderer, Markus; Hülsmann, Martin; Neuhold, Stephanie; Adlbrecht, Christopher; Strunk, Guido; Goliasch, Georg; Gisslinger, Heinz; Steger, Günther G; Hejna, Michael; Köstler, Wolfgang; Zöchbauer-Müller, Sabine; et al.
Abstract : Objective: Patients with cancer may display elevated levels of B-type natriuretic peptide (BNP) and high-sensitive troponin T (hsTnT) without clinical manifestation of cardiac disease. This study aimed to evaluate circulating cardiovascular hormones and hsTnT and their association with mortality in cancer. Methods: We prospectively enrolled 555 consecutive patients with a primary diagnosis of cancer and without prior cardiotoxic anticancer therapy. N-terminal pro BNP (NT-proBNP), mid-regional pro-atrial natriuretic peptide (MR-proANP), mid-regional pro-adrenomedullin (MR-proADM), C-terminal pro-endothelin-1 (CT-proET-1), copeptin, hsTnT, proinflammatory markers interleukin 6 (IL-6) and C reactive protein (CRP), and cytokines serum amyloid A (SAA), haptoglobin and fibronectin were measured. All-cause mortality was defined as primary endpoint. Results: During a median follow-up of 25 (IQR 16–31) months, 186 (34%) patients died. All cardiovascular hormones and hsTnT levels rose with tumour stage progression. All markers were significant predictors of mortality with HRs per IQR of 1.54 (95% CI 1.24 to 1.90, p<0.001) for NT-proBNP, 1.40 (95% CI 1.10 to 1.79, p<0.01) for MR-proANP, 1.31 (95% CI 1.19 to 1.44, p<0.001) for MR-proADM, 1.21 (95% CI 1.14 to 1.30, p<0.001) for CT-proET-1, 1.22 (95% CI 1.04 to 1.42, p=0.014) for copeptin and 1.21 (95% CI 1.13 to 1.32, p<0.001) for hsTnT, independent of age, gender, tumour entity and stage, and presence of cardiac comorbidities. NT-proBNP, MR-proANP, MR-proADM and hsTnT displayed a significant correlation with IL-6 and CRP. Conclusions: Circulating levels of cardiovascular peptides like NT-proBNP, MR-proANP, MR-proADM, CT-pro-ET-1 and hsTnT were elevated in an unselected population of patients with cancer prior to induction of any cardiotoxic anticancer therapy. The aforementioned markers and copeptin were strongly related to all-cause mortality, suggesting the presence of subclinical functional and morphological myocardial damage directly linked to disease progression.